HUBUNGAN HASIL BELAJAR OPERASI HITUNG PECAHAN DENGAN HASIL BELAJAR FISIKA SISWAPADA TOPIK SUHU DAN PENGUKURANNYA - Effendi, Yudi Andri Anto, Erwin & (UNIVERSITAS SLAMET RIYADI, 2016)
The material in learning about temperature and measurement are one of the dificultmaterials in physic subject of the seventh grade students of MTs Islamiyah Sumber Mulyo,because it has closely relationship that be the difficult subject in Math. The objective of this studyis to know wheter there is a significant correlation or not between the fraction operationachievement and the students’ physic achievement with the topic ‘ temperature and measurement’of the seventh grade students of MTs Islamiyah Sumber Mulyo in academic year 2014/2015.Method of the study is quantitatif research and the population is all of the seventh grade studentsof MTs Islamiyah Sumber Mulyo. The random sampling technique was used. In collecting of thedata, the writers used the test to VIIB as the sample. It measured by using Pearson ProductMoment formula, regression equation, determination coeffision and ttest. Based on the calculationof the data, it was found that there is a significant correlation between the fraction operationachievement and the students’ physic achievement by the topic ‘ temperature and measurement’.Key Words : the fraction operation, students’ physic achievement, and temperature andmeasurement.